Benchmarking of virome metagenomic analysis approaches using a large, 60+ members, viral synthetic community - Schönegger, Deborah; Moubset, Oumaima; Margaria, Paolo; Menzel, Wulf; Winter, Stephan; Roumagnac, Philippe; Marais, Armelle; Candresse, Thierry (Journal of virology, 2023)
We report here efforts to benchmark performance of two widespread approaches for virome analysis, which target either virion-associated nucleic acids (VANA) or highly purified double-stranded RNAs (dsRNAs). This was achieved using synthetic communities of varying complexity levels, up to a highly complex community of 72 viral agents (115 viral molecules) comprising isolates from 21 families and 61 genera of plant viruses. The results obtained confirm that the dsRNA-based approach provides a more complete representation of the RNA virome, in particular, for high complexity ones. However, for viromes of low to medium complexity, VANA appears a reasonable alternative and would be the preferred choice if analysis of DNA viruses is of importance. Several parameters impacting performance were identified as well as a direct relationship between the completeness of virome description and sample sequencing depth. The strategy, results, and tools used here should prove useful in a range of virome analysis efforts.